Enhanced Performance of All‐Solution Processed Multilayer OLEDs by Photoluminescence Lifetime Reduction of Cu(I) Complex Emitters Containing Chalcogenolate‐Diimine Ligands. Issue 33 (19th August 2021) - Salla, Cristian A. M.; Farias, Giliandro; Pereira, Alessandra; Cremona, Marco; Quirino, Welber G.; Legnani, Cristiano; de Souza, Bernardo; Bechtold, Ivan H.
Abstract: Luminescent and solution‐processable copper(I) complexes offer the perspective of obtaining devices that combine efficiency and stability at low production costs. Here, we investigate Cu(I) complexes with phosphine and 1, 10‐phenanthroline‐derived ligands, which show thermally activated delayed fluorescence (TADF) and phosphorescence applied to all‐solution processed multilayer OLEDs. Unsubstituted, thiadiazole‐substituted and selenodiazole‐substituted phenanthroline ligands were compared to evaluate the potential of the incorporation of sulfur and selenium atoms to enhance the device performance. A shortening of the photoluminescence lifetime of the selenium‐containing emitter was found to compensate this emitter's lower emission yield, leading to devices of comparable performance to devices based on the more efficiently emitting unsubstituted phenanthroline complex. The results indicate that the emission lifetime reduction is a promising approach to improve OLEDs based on solution‐processable Cu(I) complexes. Abstract : We explored Cu(I) complexes with phosphine and 1, 10‐phenanthroline‐derived ligands as emitters in all‐solution processed multilayer OLEDs. The photoluminescence lifetime reduction of the selenium‐containing emitter compensated the lower emission yield and improving OLED performance. The table of contexts illustrates the selenium‐ligand emitter, the solution processing and the OLED emission.